Activity Origin and Catalyst Design Principles for Electrocatalytic Oxygen Evolution on Layered Transition Metal Oxide with Halogen Doping. Issue 9 (20th July 2021) - Zhao, Zebi; Chang, Haonan; Wang, Ruyue; Du, Peng; He, Xian; Yang, Jingkai; Zhang, Xinlai; Huang, Kai; Fan, Dongyu; Wang, Yonggang; Pan, Xuchao; Lei, Ming
Abstract : The electronic structure of transition meatal oxides is in the predominant position among mostly central reactions, such as oxygen electroncatalysis, for the applications in energy storage. Herein, cobalt‐based catalysts are developed by taking the advantage of the strong electronegativity of halogen elements, whose activity and stability are also guaranteed. A "theory–calculation–experiment" research system is proposed to sort out the relationship between the electronegativity of heteroatoms and the electronic structure of layered CoO/F, CoO/Cl, and CoO/Br, for the electrochemical oxygen evolution reaction (OER). Experiments corresponding to calculations also verify that the stronger the electronegativity of the halide ions in the cobalt oxide catalyst, the more obvious the improvement of OER performance. By understanding the electronegative screening of halogen modification, a new perspective on designing principles for water‐splitting devices based on bandgap‐engineered metal oxides is proposed. Abstract : A schematic diagram of 2D cobalt oxy‐halide nanosheets is shown. The outstanding oxygen evolution reaction (OER) performance of CoO/F nanosheets can be ascribed to a closer O p ‐band center relative to the Fermi level and thus an enhanced CoO hybridization due to the decreased charge transfer gap between oxygen 2 p and cobalt 3 d states.